2001
DOI: 10.1007/pl00020977
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Current-Voltage Characteristics of Charophyte Membranes. II. The Effect of Salinity on Membranes of Lamprothamnium papulosum

Abstract: Lamprothamnium is a salt-tolerant charophyte that inhabits a broad range of saline environments. The electrical characteristics of Lamprothamnium cell membranes were modeled in environments of different salinity: full seawater (SW), 0.5 SW, 0.4 SW, and 0.2 SW. The cells were voltage-clamped to obtain the I/V (current-voltage) and G/V (conductance-voltage) profiles of the cell membranes. Cells growing at the different salinities exhibited one of three types of I/V profiles (states): pump-, background- and K(+)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 46 publications
2
44
0
Order By: Relevance
“…There was residual conductance when both inhibitors were present; this could be due to a ''leak'' conductance, as seen in charophytes (Beilby 1989;Beilby and Shepherd, 2001;Beilby et al in press). Infusion of the inhibitors into the vacuole has no effect on G TP , but it is not clear whether this is because the tonoplast channels are not sensitive to them, or because the inhibitor exposure was too short for it to diffuse through the vacuolar mucilage.…”
Section: Models Of Ion Transportmentioning
confidence: 96%
See 1 more Smart Citation
“…There was residual conductance when both inhibitors were present; this could be due to a ''leak'' conductance, as seen in charophytes (Beilby 1989;Beilby and Shepherd, 2001;Beilby et al in press). Infusion of the inhibitors into the vacuole has no effect on G TP , but it is not clear whether this is because the tonoplast channels are not sensitive to them, or because the inhibitor exposure was too short for it to diffuse through the vacuolar mucilage.…”
Section: Models Of Ion Transportmentioning
confidence: 96%
“…There is an increase in H + -pumping, which drives increased passive K + uptake and Cl ) uptake by H + symport (Beilby & Shepherd, 2001). Valonia and Ventricaria PDs become more positive, possibly due to an increase in active K + uptake at the tonoplast.…”
Section: Comparisons Between Salt-tolerant Charophytes and Valonia/vementioning
confidence: 99%
“…Nonetheless, at all salinities studied, some Lamprothamnium cells were in the background or the K + state and the pump did not seem to work at all (Beilby and Shepherd 2001b). These cells were always monitored for good streaming rates to ensure that they were not damaged.…”
Section: Increase In Salinitymentioning
confidence: 94%
“…2). Beilby and Shepherd (2001a) modelled the I/V profiles of Lamprothamnium cells acclimated to salinities ranging from 0.2 to full ASW (artificial sea water). They found that the cells could be in three different states: (1) pump state, (2) background state or (3) K + state (each state displaying typical I/V characteristics, see Chap.…”
Section: Increase In Salinitymentioning
confidence: 99%
“…Right panel: In the halophyte S. maritima, the VIC appears to be absent and Na + influx occurs only through the IRC. Large pump activity hyperpolarises the membrane by an increase in Na + concentration (Beilby and Shepherd 2001), so cells must be able to monitor Na + concentration. This activation persists as long as the cells stay in the high salt medium.…”
Section: Ion Channels and Salt Tolerance In Charophytesmentioning
confidence: 99%